Radial Infall onto a Massive Molecular Filament. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Battersby, Cara; Myers, Philip C.; Shirley, Yancy L.; Keto, Eric; Kirk, Helen
Abstract: The newly discovered Massive Molecular Filament (MMF) G32.02+0.05 (~ 70 pc long, 10 5 M⊙ ) has been shaped and compressed by older generations of massive stars. The similarity of this filament in physical structure (density profile, temperature) to much smaller star-forming filaments, suggests that the mechanism to form such filaments may be a universal process. The densest portion of the filament, apparent as an Infrared Dark Cloud (IRDC) shows a range of massive star formation signatures throughout. We investigate the kinematics in this filament and find widespread inverse P cygni asymmetric line profiles. These line asymmetries are interpreted as a signature of large-scale radial collapse. Using line asymmetries observed with optically thick HCO + (1-0) and optically thin H 13 CO + (1-0) across a range of massive star forming regions in the filament, we estimate the global radial infall rate of the filament to range from a few 100 to a few 1000 M⊙ Myr −1 pc −1 . At its current infall rate the densest portions of the cloud will more than double their current mass within a Myr.